Identifikasi Rumah Layak Huni di Gampong Lampulo, Banda Aceh - Idawati, Dyah Erti; Aditya, Atika; Dewi, Cut; Irwansyah, Mirza; Mahmud, Mirza; Batara Nurfajri Arisaputri, Sri; Mazaya, Ulfa; Maharani, Lisa (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
This community service activity was carried out in Lampulo Village, specifically in T. Teungoh Hamlet, Banda Aceh City, to identify the condition of habitable houses and analyze the factors influencing housing quality in coastal communities. Lampulo is a densely populated area where most residents work as fishermen, and it continues to face challenges such as limited space, deteriorating building quality, and inadequate access to sanitation and clean water. The program was implemented through stages of coordination with village officials and related agencies, field observations of housing and environmental conditions, and public hearings with community members to verify findings and gather local perspectives. The results of the identification show significant variations between habitable and non-habitable houses. Habitable houses generally have solid permanent structures, reliable access to clean water, adequate sanitation, and sufficient space in line with the minimum standard of 9 m per person. In contrast, non-habitable houses are characterized by structural damage, poor ventilation and lighting, inadequate sanitation, and high occupant density. Beyond physical conditions, socio-economic factors, housing ownership status, and land legality also play a crucial role in determining housing habitability. These findings highlight the importance of housing quality improvement strategies in coastal areas that not only focus on building standards but also address socio-economic conditions and land tenure security. This community service program is expected to serve as a foundation for local governments and stakeholders in formulating sustainable policies for improving coastal settlement environments.